2010
DOI: 10.1007/s10549-009-0710-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative assessment enables early diagnosis and recovery of shoulder function in patients with breast cancer

Abstract: Purpose-To determine the extent and time course of upper limb impairment and dysfunction in women being treated for breast cancer, and followed prospectively, using a novel physical therapy surveillance model post-treatment.Patients and Methods-Subjects included adult women with newly diagnosed, untreated, unilateral, Stage I to III BC and normal physiological and biomechanical shoulder function. Subjects were excluded if they had a previous history of BC, or prior injury or surgery of the affected upper limb.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
93
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 56 publications
1
93
0
2
Order By: Relevance
“…(9) A hipomobilidade do membro, provocada pela imobilização prolongada, por medo de sentir dor ou ocorrer deiscĂȘncia da cirurgia, assim como o tipo de cirurgia, o tamanho da incisĂŁo, realização de linfonodectomia axilar e traumatismos no nervo torĂĄcico longo, levam a esta limitação. (8,10) A redução da ADM provoca impacto negativo na funcionalidade dos indivĂ­duos acometidos. (11,12) A reabilitação de pacientes mastectomizadas se dĂĄ por uma assistĂȘncia multiprofissional.…”
Section: Introductionunclassified
“…(9) A hipomobilidade do membro, provocada pela imobilização prolongada, por medo de sentir dor ou ocorrer deiscĂȘncia da cirurgia, assim como o tipo de cirurgia, o tamanho da incisĂŁo, realização de linfonodectomia axilar e traumatismos no nervo torĂĄcico longo, levam a esta limitação. (8,10) A redução da ADM provoca impacto negativo na funcionalidade dos indivĂ­duos acometidos. (11,12) A reabilitação de pacientes mastectomizadas se dĂĄ por uma assistĂȘncia multiprofissional.…”
Section: Introductionunclassified
“…The shoulder is subject to the rapid installation of stiffness and muscle atrophy after breast cancer surgery, with the flexion and abduction movements the most affected (7)(8) . The prolonged immobilization caused by fear and/or pain, as well as the type of surgery, the incision size, the performance of axillary lymphadenectomy, long thoracic nerve trauma or muscle spasm throughout the cervical region, arising from the muscular defense reaction, are factors that cause women to have a tendency toward little movement of the upper limb (9)(10) . To decrease the 37 www.eerp.usp.br/rlae Petito EL, NazĂĄrio ACP, Martinelli SE, Facina G, GutiĂ©rrez MGR.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease the 37 www.eerp.usp.br/rlae Petito EL, NazĂĄrio ACP, Martinelli SE, Facina G, GutiĂ©rrez MGR. incidence of these complications, studies highlight that the performance of exercises immediately after surgery gives positive results, both in the physical and the psychological areas, since it provides conditions for the woman to return to their activities of daily living (ADLs) within a shorter period of time (4,9,11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These preliminary findings are supported in previous research by Springer and colleagues that found significant improvements in shoulder function; 3 however, while this study was prospective in design, it had no control group. 3 Beurskens and colleagues 4 have also reported beneficial effects of physiotherapy with postoperative intervention, but no preoperative intervention was included in their study.…”
mentioning
confidence: 99%